Edusyiarpeneur Masyarakat Melalui IRD Batik Motif Keulamaan - Indriya, Indriya (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
It is research that focuses on the creation of research-based works of art carrying the concepts of education, da'wah as well as economic value. The work created is IRD batik with the Ulamaan motif which has contributed to innovation in the development of batik motifs in Indonesia. It is hoped that the development of this batik motif can be used as a basis for making new products as a media for education and broadcast as well as a part of moving the community's economy. There are three stages in the method of creating works of art, namely experimentation, contemplation, and embodiment. From this method the author will develop Ulamaan batik motifs into new products that have edusyiarpreneur content. This research was conducted using a qualitative approach, and creator theory with an attempt to describe the reconstruction of Islamic Education values in batik motifs. Data collection was carried out through observation, literature study, interviews, and documentation, and was analyzed descriptively. The authors found this in the reconstruction of Islamic Education values which can be applied to a batik motif. The philosophies that can be applied to Islamic Education motifs or decorations include, (1) applicative transformation of Islamic Education through its batik motifs (education); (2) Education is characterized by the values of the teachings of the Ulama (syiar), (3) The existence of batik as an ancestral cultural heritage must continue to be preserved, one of which is IRD Batik, as a work of education, preaching as well as having economic value (preneur). Keywords: Batik, IRD Batik Motives of Religion, Edusyiarpreneur